Concurrent chemoradiation in treatment of carcinoma cervix - Singh, Meeta; Jha, Rajshree; Baral, Josie; Rawal, Suniti (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: to compare if concurrent chemoradiation is better than radiotherapy given alone in the treatment of women with locally advanced cervical cancer from published literature Method: Study Design: Randomized control trials of > than 2, 403 women participants who underwent treatment for advanced cervical carcinoma mainly in two huge center i.e. from National Cancer Institute (NCI), USA and European Organization for Research and Treatment of Cancer (EORTC) were reviewed regarding the treatment they received at the center: concurrent chemoradiation/ radiation therapy alone. The results were analyzed to come to conclusion. Result demonstrated a 30-50% improvement in survival when cisplatin-based chemotherapy in NCI or 5 fluorouracil and cisplatin based chemotherapy was used in EORTC was administered with concurrent radiation therapy (chemoradiation) Conclusions: The addition of chemotherapy (cisplatin) in NCI and (cisplatin and fluorouracil) in the EORTC for the treatment of locally advanced cervical cancer with the concurrent chemoradition have elicited better survival than those treated with radiotherapy alone dittoed by several other trials which can be anticipated to benefit Nepalese women with locally advanced cervical carcinoma. Key-words: Cancer cervix, chemoradiation, radiotherapy doi:10.3126/njog.v2i1.1467 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 4 - 8 May -June 2007